2022
DOI: 10.1016/j.gim.2021.11.013
|View full text |Cite
|
Sign up to set email alerts
|

The opinions and experiences of people with intellectual disability regarding genetic testing and genetic medicine: A systematic review

Abstract: Genetic testing is frequently conducted on people with intellectual disability. This systematic literature review sought to assess what research has been conducted with people with intellectual disability to investigate their opinions and experiences of genetic counselling and testing. Methods: A search of 5 online databases (from year of database creation to 2021) yielded 1162 articles. Seven articles met the inclusion criteria. We assessed the quality, accessibility, and inclusivity of each study and extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
(103 reference statements)
0
13
0
Order By: Relevance
“…Children with intellectual disability form the majority of those currently seen by genomic healthcare services, yet our recent systematic literature review showed their opinions and preferences about genomic healthcare have not been assessed at all (5). Effective inclusive qualitative research with children with intellectual disability has been demonstrated by our group and others (8).…”
Section: Limitations the Study And Areas Of Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with intellectual disability form the majority of those currently seen by genomic healthcare services, yet our recent systematic literature review showed their opinions and preferences about genomic healthcare have not been assessed at all (5). Effective inclusive qualitative research with children with intellectual disability has been demonstrated by our group and others (8).…”
Section: Limitations the Study And Areas Of Future Researchmentioning
confidence: 99%
“…Genomics is revolutionising understanding of the underlying causes of over 50% of intellectual disability in high income countries (2,3), and can improve overall health outcomes through precision medicine, empowerment, and reproductive choice (4). People with intellectual disability risk exclusion from these opportunities through inequitable, non-inclusive genomic healthcare and lack of data on their experiences, opinions, and preferences (5). This situation breaches their rights under the United Nations Convention on the Rights of Persons with Disability (2006) (6) and Australia's Charter of Health Care Rights (7).…”
Section: Introductionmentioning
confidence: 99%
“…Factors that should be considered while conducting genetic testing of patients with developmental delay were discussed in previous studies [ 13 , 14 , 15 , 16 , 17 ]; the researchers developed the questionnaire items based on these findings [ 13 , 14 , 15 , 16 , 17 ]. The respondents’ level of concern for each factor was rated on a 5-point Likert scale (1 = not concerned at all; 5 = very concerned).…”
Section: Resultsmentioning
confidence: 99%
“…The implementation items were developed based on previous studies [ 13 , 14 , 15 , 16 , 17 ] by considering the steps the physician needed to perform while conducting genetic testing on patients with developmental delay. The 25 physicians who recommended genetic testing to patients with developmental delay in the past year responded to the items evaluating the degree to which each step was implemented when conducting genetic testing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation